Labour law, fundamental rights and social Europe - Rönnmar, Mia, 1973- (Swedish studies in European law, 2011)
This volume, comprising three parts and ten chapters, all of them peer-reviewed essays, arises from the work of the Swedish Network for European Legal Studies. Its focus is on labour and social security law. The chapters, written by distinguished legal researchers associated with Swedish universities, provide insight into a range of topical and important developments, seeking new and interesting perspectives. Sweden has been a member of the European Union since 1995, and EU law and European law perspectives have been well integrated into Swedish labour law and social security law research. Wit.